Regeneration and transient gene expression of African Musa species with diverse genomic constitution and ploidy levels - Tripathi, L.; Tripathi, J.N.; Hughes, J.A.; Keese, P.; Oso, R.T. (2003)
An efficient regeneration protocol, which appeared to be independent of ploidy level and genomic background was developed for Musa spp using apical meristems. The selected species represented major groups of Musa including fertile diploid bananas (AA and BB genomes) , the sterile triploid plantain (AAB) , Cavendish bananas (AM), and tetraploid hybrids (AAAA and AAAB). Multiple shoot regeneration was most efficient from explants cultured on Murashige and Skoog medium supplemented with 5 mg L -1 of 6-benzylaminopurine. More than 98% shoots transferred to medium supplemented with indole-3-butyric acid developed roots. Transient expression of the 13 glucuronidase (gus A) gene was observed in 60-70% of explants, 48 h after microprojectife bombardment. Organogenesis from apical shoot meristems may offer a simple efficient method for easier transformation of a broad range of Musa spp than the use of embryogenic cell suspensions.